2008
DOI: 10.1111/j.1462-5822.2008.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-dependent entry of a gingipain adhesin peptide andPorphyromonas gingivalisinto host cells

Abstract: SummaryPorphyromonas gingivalis, a Gram-negative oral anaerobe, is associated with periodontitis, a disease that in some form affects up to 80% of the adult population in the USA. The organism interacts with gingival epithelium and surrounding tissue, and in this study we analysed interactions initiated by P. gingivalis and by a peptide derived from the adhesin domain of arg-gingipain A, a member of a family of surface cysteine proteinases. Recombinant peptide A44 blocked adherence of bacteria to host cell mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…gingivalis pathogenicity and more recently for their role in cell invasion (Boisvert & Duncan, 2008;Fitzpatrick et al, 2009;Chen & Duncan, 2004). In light of their importance in this process we decided to examine whether the levels of these proteases might be altered in the invasive and noninvasive subtypes compared with isogenic wild-type strains.…”
Section: Stability Of the Invasive Phenotypementioning
confidence: 99%
“…gingivalis pathogenicity and more recently for their role in cell invasion (Boisvert & Duncan, 2008;Fitzpatrick et al, 2009;Chen & Duncan, 2004). In light of their importance in this process we decided to examine whether the levels of these proteases might be altered in the invasive and noninvasive subtypes compared with isogenic wild-type strains.…”
Section: Stability Of the Invasive Phenotypementioning
confidence: 99%
“…It is known that the gingipain adhesin fragment A44 binds to and is internalized by HEp-2 cells in a dose-and time-dependent manner (17). Moreover, A44 can directly bind to host FN (7). To identify potentially novel binding partners, protein capture with the use of A44 as bait was performed (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Binding partners for fimbriae include fibronectin (FN) and its cognate receptor α5β1 integrin (5,6,(10)(11)(12). The adhesin domains of arg-gingipain A and lys-gingipain were shown to bind to epithelial cells, and the adhesin peptide A44 of the former has a high affinity for host FN (7,13). In addition to integrins and ECM proteins, P. gingivalis interacts with several other receptors (14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that both proteolytic activation of PAR-2 by gingipains and the endocytosis of P. gingivalis are required for the up-regulation of IL-33 expression induced by P. gingivalis in oral epithelial cells. P. gingivalis enters gingival epithelial cells by endocytosis, which mediates binding of Rgp to the cells [22]. It must be noted that gingipains are required for maturation of P. gingivalis fimbriae [23], which is essential for internalization of the bacterium into epithelial cells [24].…”
Section: Role Of Par-2 In the Induction Of Il-33 By Gingipainsmentioning
confidence: 99%